2017
DOI: 10.1016/j.injury.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Status of trauma quality improvement programs in the Andean region: What foundation do we have to build on

Abstract: Introduction Trauma quality improvement (QI) programs have been shown to improve outcomes and decrease cost. These are high priorities in low- and middle-income countries (LMICs), where 2,000,000 deaths due to survivable injuries occur each year. We sought to define areas for improvement in trauma QI programs in four LMICs. Methods We conducted a survey among trauma care providers in four Andean middle-income countries: Bolivia, Colombia, Ecuador, and Peru. Results 336 physicians, medical students, nurses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…168 Studies identified in this review used these guidelines to both study what QI activity undertaken as well as studies applying recommended QI practices such as preventable death panels. 70 72 114 140 162 The other non-study literature identified had not been applied for health system assessment by studies in this review. 14 169–171…”
Section: Resultsmentioning
confidence: 99%
“…168 Studies identified in this review used these guidelines to both study what QI activity undertaken as well as studies applying recommended QI practices such as preventable death panels. 70 72 114 140 162 The other non-study literature identified had not been applied for health system assessment by studies in this review. 14 169–171…”
Section: Resultsmentioning
confidence: 99%
“…Another key theme was the importance of adaptability. A focus on tailoring the intervention to the local context to ensure success and sustainability was apparent [9,16,21,22,30,33,35,36]. The implementation of a multi-hospital injury surveillance program in Mozambique was driven by local data collectors that enhanced the sustainability of the project [16].…”
Section: Resultsmentioning
confidence: 99%
“…Increased dissemination of results is a critical facilitator to establish prolonged TQIP support, through enhancing engagement and QI understanding. A trauma care provider survey in the Andean region concluded that increased QI dissemination can empower local providers to participate in health systems and drive change [35]. The increase in peer-reviewed QI reports from LMICs emphasises dissemination through publications as a viable means of providing guidance for future programs and expanding QI knowledge [45].…”
Section: Domain 5: Process Of Implementationmentioning
confidence: 99%
“…This project represents ''phase two'' of a multi-phase project to implement quality M&M conferences in Peru. Phase one included a baseline assessment of existing practices in Peru and Latin America and a review of global implementation of the WHO TQIP guidelines [11][12][13]. It revealed standardized case selection criteria, documentation of M&M conclusions and a clear plan for follow-up to predict M&M conferences which are perceived to result in institutional change [11][12][13].…”
Section: Methodsmentioning
confidence: 99%